Species-dependent tunneling ionization of weakly bound atoms in the short-wave infrared regime - D Zille; D Adolph; S Skruszewicz; A M Sayler; G G Paulus (New Journal of Physics, 2020)
We investigate the intensity- and species-dependent strong-field ionization of alkali metal atoms; sodium, potassium, rubidium and caesium; by intense, few-cycle laser pulses in the short-wave infrared (sw-IR) regime at 1800 nm. The low ionization potential, I _p , of these atoms allows us to scale the interaction and study the tunneling regime at sw-IR wavelengths using low intensities and pulse energies. Measurements of above-threshold ionization spectra in the alkali species exhibit distinct differences to rare gas spectra at 800 and 1800 nm. However, pairing the low ionization potential of these atoms with longer wavelengths results in the reemergence of some well-know features of nobel gas spectra in the visible, e.g., the plateau. Our focus lies on the comparison of high-energy rescattered electron yield among the different alkali species. The highly unfavorable plateau scaling known from rare gases at longer wavelengths is successfully circumvented by switching to low- I _p targets. In the investigated parameter range, we identify potassium as the most efficient rescatterer. In addition, this paves the way to a carrier-envelope phasemeter operating in the sw-IR/mid-wave IR regime, employing alkali metal atoms as a target.